Correction to: Identifying common barriers and facilitators to linkage and retention in chronic disease care in western Kenya - Beth Rachlis; Violet Naanyu; Juddy Wachira; Becky Genberg; Beatrice Koech; Regina Kamene; Jackie Akinyi; Paula Braitstein (BMC, 2018)
After the publication of the original article [1], it was highlighted that Fig. 1 was incorrectly labeled.